Fatty acid and triacylglycerol comparison of infant formulas on the Chinese market. (August 2019) - Chen, Yujie; Zhang, Xin; Li, Donggang; Yi, Huaxi; Xu, Tao; Li, Siming; Zhang, Lanwei
Abstract: Fatty acid (FA) and triacylglycerol (TAG) composition plays an important role in the nutritional value of infant formulas. The profiles of FAs and TAGs, and regioisomers (rac) of dioleoyl-palmitoylglycerol (OPO) and dipalmitoyl-oleoylglycerol (PPO) in ten brands of infant formulas were analysed and compared between infant formulas labelled as containing rac-OPO (OPO-Fs) or not labelled as such (OPO-NFs). The predominant difference was that OPO-Fs mainly contained rac-OPO (∼70%) and rac-PPO (>95%), while OPO-NFs mainly contained rac-OOP (65.24–100%) and rac-POP (∼90%). With rac-OPO supplementation, the levels of saturated FAs (especially palmitic acid) and TAGs improved. The same results were observed in infant formulas supplemented with palm searin. The levels of short chain FAs, odd-numbered saturated FAs, stearic, myristoleic and palmitoleic acids were mainly affected by the basic materials of infant formulas. Coconut and palm kernel oil addition enhanced the concentrations of medium chain FAs and TAGs.